2015
DOI: 10.5352/jls.2015.25.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidative Activities of the Extracts from Walnut (Juglans regia L.) Green Husk

Abstract: Several studies suggest that regular consumption of walnuts may have beneficial effects against oxidative stress-mediated disease such as cancer. The present study reports the total phenolic and flavonoid contents, together with the antioxidant and antibacterial activities of several solvent extracts (methanol, n-hexane, ethyl acetate, n-butanol, and water) obtained from walnut (Juglans regia L.) green husk. MIC (minimal inhibitory concentration) values of the walnut extracts for 8 human pathogenic bacteria st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The sample extracted with EtOAc had the highest antioxidant potential (EC 50 = 13.43 μg/mL for 1,1diphenyl-2-picrylhydrazyl and EC 50 = 41.83 μg/mL for 2,2'-azinobis-(3-ethylbenzthiazoline-6-sulphonate) radical scavenging activity assay). 29 In addition, some scholars used the common method, reflux method, and ultrasonic method to verify the influence of different extraction methods on the extraction rate of total flavonoid and juglone (1) in WGH. The results showed that the contents of total flavonoid and juglone in the extract obtained by the ultrasonic extraction method were higher than those of the other 2 methods.…”
Section: Harvesting Period Pretreatment and Extraction Of Wghmentioning
confidence: 99%
“…The sample extracted with EtOAc had the highest antioxidant potential (EC 50 = 13.43 μg/mL for 1,1diphenyl-2-picrylhydrazyl and EC 50 = 41.83 μg/mL for 2,2'-azinobis-(3-ethylbenzthiazoline-6-sulphonate) radical scavenging activity assay). 29 In addition, some scholars used the common method, reflux method, and ultrasonic method to verify the influence of different extraction methods on the extraction rate of total flavonoid and juglone (1) in WGH. The results showed that the contents of total flavonoid and juglone in the extract obtained by the ultrasonic extraction method were higher than those of the other 2 methods.…”
Section: Harvesting Period Pretreatment and Extraction Of Wghmentioning
confidence: 99%
“…The nut is surrounded by the green husk that contains many bioactive compounds, such as polyphenols, which include flavonoids, [ 6 , 7 ], also known as phenolics [ 8 , 9 , 10 ], and pectin, glucans [ 5 ] and chlorophyll [ 11 ]. The phytochemicals have antimicrobial, antifungal and antioxidant activities [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic compounds play an important role in the plant defence mechanisms against stress caused by many environmental factors and various pathogens [ 20 ]. They can inhibit the growth of mycelia and different bacteria up to 50%, but it is indicated that their inhibition effects depend on their concentration and the relationship between the juglone and phenolics present in the plant tissue [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%